2013
DOI: 10.15376/biores.8.4.6211-6219
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Solvents on Cypress Liquefaction to Fuels and Characterization of Products

Abstract: This study investigated the effects of various solvents on cypress liquefaction in the range of 180 to 300 °C. The solid residues and bio-oils obtained from cypress liquefaction were characterized to investigate the mechanism of the liquefaction process. Results obtained using FT-IR, sugar analysis, and elemental analysis showed that the solvent could affect both the formation of various compounds in the bio-oil and the product distribution during the cypress liquefaction process. Considering the bio-oil yield… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…The defatted corn hull was dried at 105°C for 24 h and kept in desiccators at room temperature before used. The composition analysis of defatted corn hull was performed according to Liu et al [2013]. The total dietary fi ber was determined according to AOAC method 985.…”
Section: Methodsmentioning
confidence: 99%
“…The defatted corn hull was dried at 105°C for 24 h and kept in desiccators at room temperature before used. The composition analysis of defatted corn hull was performed according to Liu et al [2013]. The total dietary fi ber was determined according to AOAC method 985.…”
Section: Methodsmentioning
confidence: 99%
“…It has been found that more chemical materials can be obtained in supercritical acetone than in supercritical ethanol under the same reaction condition. Meanwhile, the solvent could affect the formation of various compounds in the bio-oil (26,27). To best of our knowledge, there have been few studies about the mechanism of cellulose liquefaction in supercritical acetone, and the selectivity of acetone on platform chemicals formation in bio-oil is also not clarified.…”
Section: Introductionmentioning
confidence: 99%